Dampak Liberalisasi Perdagangan Susu terhadap Peternak Lokal di Boyolali : Studi Kasus Kebijakan Impor - Putri Rahayu; Bekti Pangestu; Ridha Alfisya Rasyidin; Sarpini (CV. KAMPUS AKADEMIK PUBLISING, 2024)
International trade plays a crucial role in the economic growth of a country, including Indonesia. However, in recent decades, the national dairy industry has faced increasingly complex challenges due to trade liberalization and import policies. The impact of this policy was the milk dumping case that occurred in Boyolal. This incident attracted national attention and raised fundamental questions regarding the sustainability of the dairy farming sector in Indonesia. Using the narrative literature review method, namely comparing and analyzing previously existing theories. The literature review study used is conducting a comprehensive literature review on the topic discussed, including reference sources such as scientific journals, books and other references. International Trade, Trade Liberalization Concept. Milk Trade Liberalization Policy in Indonesia, Especially Regarding Imports, Dairy Cattle Farmers, Boyolali, Impact of Import Policy on Dairy Cattle Farmers, dairy farmers protest the policy of restricting local milk quotas to the Industrial Processing Industry (IPS). This policy causes local cow's milk to not be absorbed by factories, to accumulate and be wasted. Government policy solution for local Boyolali milk farmers. International trade plays an important role in the economic growth of a country, including Indonesia. However, the dairy industry in Indonesia has faced complex challenges in recent decades due to trade liberalization and import policies. The most significant impact of this policy was the dumping of excess milk in Boyolali, Central Java. strict on milk imports, introducing import tariffs protects local farmers from unfair price competition.